Comparison of Four Foraminiferal Biotic Indices Assessing the Environmental Quality of Coastal Mediterranean Soft Bottoms - Briz Parent (MDPI AG, 2021)
Coastal environments are exposed to numerous pressures that potentially affect marine soft bottom faunas. Among these pressures, organic matter enrichment is very frequent. Several indices based on living (Rose Bengal-stained) foraminiferal communities have recently been developed to assess the induced impact and determine the environmental quality of these environments. Here, we use an open waters Mediterranean Sea data set to test the benefits and drawbacks of four foraminiferal indices: (1) the effective number of species (exp(H’bc)), (2) the Tolerant Species Index for the Mediterranean (TSI-Med), (3) the Foraminifera AMBI (Foram-AMBI), and (4) the Foram Stress Index (FSI). These indices all intend to measure the response of the foraminiferal communities to organic matter enrichment, and therefore, their results should be very similar. We found that the diversity-based index, exp(H’bc), was not suitable to evaluate the environmental quality of our Mediterranean coastal settings, as it had a non-monotonic relationship with the organic matter enrichment gradient. The three indices based on groups of indicator species (TSI-Med, Foram-AMBI, and FSI) yielded fairly similar results. For Foram-AMBI, using only assigned species to calculate proportions of indicator species partly avoided to misinterpret the results. In TSI-Med, a correction based on sediment grain size is applied to distinguish between natural and anthropogenic organic enrichment. Such a correction could also be added to Foram-AMBI and FSI. The limits between the Ecological Quality Status (EQS) classes used for macrofauna were not adapted for Foram-AMBI. Here, we propose new EQS class limits for the Foram-AMBI as follows: very good: 0 ≤ x < 1.4; good: 1.4 ≤ x < 2.4; moderate: 2.4 ≤ x < 3.4; poor: 3.4 ≤ x < 4.4; bad: 4.4 ≤ x ≤ 6. These limits could evolve in the future as new data become available, especially with a poor and bad environmental quality.